ChemInform Abstract: Magnesium‐rich Intermetallics RE3RuMg7 (RE: Y, Nd, Dy, Ho) — Rows of Condensed Ru@RE6/2 Octahedra in Magnesium Matrices. Issue 11 (18th March 2014) - Kersting, Marcel; Rodewald, Ute Ch.; Schwickert, Christian; Poettgen, Rainer
Abstract The title compounds are synthesized from the elements (Nb tubes, 1273 K for 2 h, 673 K for 5 h) and characterized by powder XRD, and single crystal XRD for the Dy compound.